2016
DOI: 10.1021/acs.analchem.6b00123
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Northern Continental Air Standard Reference Material

Abstract: The National Institute of Standards and Technology (NIST) recently began to develop standard mixtures of greenhouse gases as part of a broad program mandated by the 2009 United States Congress to support research in climate change. To this end, NIST developed suites of gravimetrically assigned primary standard mixtures (PSMs) comprising carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) in a dry-natural air balance at ambient mole fraction levels. In parallel, the National Oceanic and Atmospheric Adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 25 publications
(39 reference statements)
0
34
0
Order By: Relevance
“…NIST has a long history of producing synthetic greenhouse gas mixture SRMs (CO 2 , CH 4 , and N 2 O) based on gravimetric preparation. Recently, Rhoderick et al [3,4] reported the first CRMs for whole natural air with values assigned for greenhouse gases, denoted as SRM 1720 Northern Hemisphere Air [3] and SRM 1721 Southern Oceanic Air [4]. These unique SRMs consist of batches of 30 cylinders of pristine ambient air collected at two remote locations: (1) Niwot Ridge (CO, USA) for SRM 1720 and Baring Head, New Zealand for SRM 1721.…”
Section: Novel Matrix Crmsmentioning
confidence: 99%
See 3 more Smart Citations
“…NIST has a long history of producing synthetic greenhouse gas mixture SRMs (CO 2 , CH 4 , and N 2 O) based on gravimetric preparation. Recently, Rhoderick et al [3,4] reported the first CRMs for whole natural air with values assigned for greenhouse gases, denoted as SRM 1720 Northern Hemisphere Air [3] and SRM 1721 Southern Oceanic Air [4]. These unique SRMs consist of batches of 30 cylinders of pristine ambient air collected at two remote locations: (1) Niwot Ridge (CO, USA) for SRM 1720 and Baring Head, New Zealand for SRM 1721.…”
Section: Novel Matrix Crmsmentioning
confidence: 99%
“…These unique SRMs consist of batches of 30 cylinders of pristine ambient air collected at two remote locations: (1) Niwot Ridge (CO, USA) for SRM 1720 and Baring Head, New Zealand for SRM 1721. Rhoderick et al [3,4] described the process of assigning certified values to each individual cylinder based on calibrating the instrumentation using a suite of gravimetrically-prepared NIST primary reference gas mixtures. The nominal values for the three gases were nearly identical for CO 2 (388 μmol/mol) and N 2 O (323 μmol/mol) in both SRMs, and the value for CH 4 in SRM 1720 is 5.6% higher (1860 μmol/mol).…”
Section: Novel Matrix Crmsmentioning
confidence: 99%
See 2 more Smart Citations
“…To take full profit of these observations, the uncertainty of these measurements must be minimised which implies consistent data series with traceability to common reference standards. Within the GAW Programme, Central Calibration Laboratories (CCLs) provide reference standards that are linked to internationally accepted calibration scales (Rhoderick et al, 2016;Rhoderick et al, 2018). In addition, World Calibration Centres (WCCs) evaluate GAW stations through independent assessments by on-10 site system-and performance audits (Buchmann et al, 2009).…”
Section: Introductionmentioning
confidence: 99%